Mechanical Design and Simulation: Exploring Innovations for the Future: Proceedings of the 4th International Conference on Mechanical Design and Simulation (Lecture Notes in Mechanical Engineering, 2025)
This book is an open access publication. This book presents innovative strategies and cutting-edge research at the intersection of mechanical engineering and simulation technologies. Aimed at addressing the current challenges and limitations in mechanical design, this book presents an array of advanced methodologies and tools that promise to revolutionize the field. From integrating artificial intelligence and machine learning for design optimization to leveraging the latest in finite element analysis for enhanced stress modelling, the proceedings highlight the pivotal role of simulation in pushing the boundaries of what is possible in mechanical design. With a strong emphasis on sustainable design practices and the utilization of additive manufacturing, this collection not only serves as an indispensable resource for engineers, researchers, and students but also marks a significant step forward in bridging the gap between traditional mechanical design principles and modern computational innovations.